COVİD 19 PANDEMİSİNİN ERKEN ÇOCUKLUK DÖNEMİ ÇOCUKLARIN DİJİTAL OYUN OYNAMA ALIŞKANLIKLARINA ETKİSİNE İLİŞKİN EBEVEYN GÖRÜŞLERİ. - YİĞİT, Nilüfer; MERCAN UZUN, Elif (Mehmet Akif Ersoy University Journal of Education Faculty)
The aim of this study is to investigate the impact of the pandemic period on the digital gaming habits of children in early childhood. The case study, which is one of the qualitative research methods, was used in data collection. The study group of the research consists of 15 parents with children of ages of 3-7, who spend time on digital games. Demographic information form and semi-structured interview form were used in data acquisition. Answers were sought for the research questions by performing interviews with parents. The answers provided by the parents were analyzed through the content analysis method. The parents stated that their children started playing digital games usually by watching videos at an early age. It was concluded that children spending more time outside prior to the pandemic period inclined towards digital games due to the restrictions. In conclusion, it was determined that there has been an increase in the digital gaming habits of children during the pandemic period and digital games have negative impacts on children. In addition, it was concluded that parents do not take enough responsibility and do not have enough knowledge of digital games. Receiving support regarding digital games is recommended for parents.